2009
DOI: 10.1039/b819704k
|View full text |Cite
|
Sign up to set email alerts
|

Gold-catalyzed cycloisomerization of alk-4-yn-1-ones

Abstract: Depending on the substitution pattern and the solvent, the gold-catalyzed cyclization of alk-4-yn-1-ones affords different oxygen heterocycles under mild reaction conditions. Alkynones with one substituent at C-3 undergo a 5-exo-dig cycloisomerization to substituted furans , whereas a 6-endo-dig cyclization to 4H-pyrans is observed with substrates bearing two substituents at C-3. In alcoholic solvents, alkylidene/benzylidene-substituted tetrahydrofuranyl ethers are formed in a tandem nucleophilic addition/cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 65 publications
0
25
0
2
Order By: Relevance
“…Alkynones with one substituent at C3 undergo a 5-exodig cycloisomerization to substituted furans. However, a 6-endo-dig cyclization to 4H-pyrans 149 is observed with alkynones 148 bearing two substituents at C3 (Scheme 18.46) [80].…”
Section: H-pyran Ring Synthesismentioning
confidence: 98%
“…Alkynones with one substituent at C3 undergo a 5-exodig cycloisomerization to substituted furans. However, a 6-endo-dig cyclization to 4H-pyrans 149 is observed with alkynones 148 bearing two substituents at C3 (Scheme 18.46) [80].…”
Section: H-pyran Ring Synthesismentioning
confidence: 98%
“…Au catalysis [103a] allows the use of milder conditions with similar high yields (Scheme 26, condition C, see also tautomerization of the ketone and the easier proto-deauration. [63] If the a-position to the triple bond is blocked, a 6-endo-dig mechanism operates and the 4H-pyrans 134 are formed. Curiously, the single substituent at the terminal position of the alkyne is enough to promote the formation of 4H-pyrans under Hg II catalyzed conditions (Scheme 28, condition B).…”
Section: Cycloalkoxylation Of Alkynylphenolsmentioning
confidence: 99%
“…Thus, alkynones with one substituent at C-3 undergo a 5 -exo-dig cycloisomerization to yield substituted furans 81 , whilst substrates bearing two substituents at C-3 undergo a 6 -endo-dig cyclization to give 4 H -pyrans 82 . By contrast, alkylidene/benzylidene-substituted tetrahydrofuranyl ethers 80 are formed in a tandem nucleophilic addition/cycloisomerization in alcoholic solvents [44]. Similarly, Belot et al reported a gold-catalyzed cyclization which led to nitro-substituted tetrahydrofuranyl ethers 84 (Scheme 15) [45].…”
Section: Reviewmentioning
confidence: 99%